Oestradiol Induced Inhibition of Neuroendocrine Marker Expression in Leydig Cells of Adult Rats - Ortega, Hugo Hector (2006)
The objectives of this work were to determine the changes in the expression of neuroendocrine markers in Leydig cell by estradiol treatment, and to determine whether testosterone is able to recover partially the effects of hormonal suppression induced by estradiol. Adult male rats were injected daily with either 50 µg of estradiol or estradiol plus testosterone propionate (25mg every 3 days) for 15 days. The animals were sacrificed and testicles were dissected and processed by routine histological protocols. FSH and LH serum levels were determined by RIA. The visualization of antigens was achieved by the streptavidin-peroxidase immunohistochemical method. Antibodies against Chromogranin A, S-100 Protein, P Substance, Synaptofisin, Neurofilament, Gliofibrillary Acidic Protein and Neuron Specific Enolase were used. The mean LH and FSH serum concentrations were consistently suppressed with hormonal treatments. Intermediate filaments (NF and GFAP) showed no difference in their expression. The expression of S-100, NSE and SYN was significantly lower in both hormone-treated groups. In estradiol-treated rats, the immunoreactivity of CrA and SP decreased significantly but was restored after testosterone supplementation. Although the nature and functions of many of these substances in Leydig cells remain unknown, these results are consistent with the hypothesis that the expression of some neuroendocrine markers is hormonally controlled. Keywords: rat – Leydig cell – neuroendocrin markers– estrogens